Synthesis, Characterization, Anticancer Activity, and Computational Study of Umbelliferone Schiff’s Bases - Yadav, Anand Kumar; Pramanik, Siddhartha Das; Roy, Partha; Khatiwada, Ranju; Adhikari, Achyut; Yadav, Paras Nath (Journal of Institute of Science and Technology, 2024)
4-Methylumbelliferrone derivatives (1a–1c) were synthesized by condensing 3-acetyl-4-methylumbelliferrone with hydroxyurea, urea, and thiourea. The synthesized new Schiff’s bases were characterized by elemental analysis, ESI-HR MS, NMR, FT-IR, UV-Vis, and evaluated for their anticancer activity against the human prostate cancer (DU145) cell line. The tested compounds 1a, 1b, and 1c exhibited good anticancer efficacy in a dose-dependent manner in the tested cell line with IC50; 122.78 μM, 109.65 μM, and 55.41μM, respectively in comparison to standard drug cisplatin. Furthermore, the ADMET profiling and Molecular Docking were carried with these synthesized compounds targeting protein Epidermal Growth Factor Receptor (EGFR) tyrosine Kinase (PDB ID 4HJO). Among these compounds, compound ‘1c’ showed better intestinal absorption, positive Caco-2 permeability and negative AMES toxicity and hepatotoxicity. Also, it exhibited better interaction with the catalytically active site, Methionine at position 769 (MET 769) along with Glutamine (GLN 767), with binding energy, –10.3 kcal/mol.